2003
DOI: 10.2337/diabetes.52.10.2539
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Aspects of Intestinal Lipoprotein Assembly in Psammomys Obesus

Abstract: Although postprandial hypertriglyceridemia is a major contributing factor in the development of atherosclerosis, little information is available on the effect of insulin resistance and diabetes on intestinal fat transport. The aim of the present study was to examine intracellular events that govern lipid transport and apolipoprotein (apo) B-48 -containing lipoprotein assembly in the small intestine of Psammomys obesus, a model of nutritionally induced insulin resistance and type 2 diabetes. Animals with normog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 33 publications
5
48
0
1
Order By: Relevance
“…In Group C, glycaemia can no longer be compensated for, in spite of the extraordinary elevation in plasma insulin. Recently, we demonstrated that the development of insulin-resistant and type 2 diabetic states led to intestinal oversecretion of apo B-48 lipoproteins in Psammomys obesus gerbils [18]. The results of the present investigation indicate the beneficial effects of diets enriched with n-3 FA on body weight, hyperglycaemia, hyperinsulinaemia and hyperlipidaemia.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In Group C, glycaemia can no longer be compensated for, in spite of the extraordinary elevation in plasma insulin. Recently, we demonstrated that the development of insulin-resistant and type 2 diabetic states led to intestinal oversecretion of apo B-48 lipoproteins in Psammomys obesus gerbils [18]. The results of the present investigation indicate the beneficial effects of diets enriched with n-3 FA on body weight, hyperglycaemia, hyperinsulinaemia and hyperlipidaemia.…”
Section: Discussionsupporting
confidence: 64%
“…Since proteasomal degradation of apo B plays a regulatory role in the early stages of apo B biosynthesis, we wondered whether this pathway is triggered by n-3 FA. The addition of N-acetyl-leucylnorleucinat and lactacystin as proteasomal inhibitors [18] suppressed the differences observed among groups, regardless of dietary regimen (Fig. 7b).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…La voie protéolytique du protéasome représente la stratégie de vigilance majeure empruntée par la cellule pour limiter la production de l'apo B. Nos recherches nous ont amenés à constater que l'intestin peut contribuer à augmenter simultanément la synthèse de l'apo B-48 et les lipoprotéines riches en TG lors de la résistance à l'insuline et du diabète de type 2. Ce phénomène, contribuant à la dyslipidémie diabétique, peut être expliqué par une diminution de la dégradation de l'apoB, assurée par le dysfonctionnement du système ubiquitine-protéasome [38].…”
Section: Protéasome Apo B Et Surproduction Des CMunclassified